DECONSTRUCTION OF OPPOSITION CHARACTERS IN JANE AUSTEN’S PRIDE AND PREJUDICE: ARE VILLAINS ALWAYS GUILTY? - Sulistyowati, Titis -; -, Rusiana (Universitas PGRI Sumatera Barat, 2024)
AbstractThis study aimed to examine the opposing characters in the classic Pride and Prejudice. This paper was a literary criticism to examine heroes and villains from many perspectives. The procedures of the study were as follows: (i) locating the opposing characters, (ii) analyzing the privileged and undermined characters, and (iii) overturning the privileged and undermined characterization hierarchy. The study discovered that the confrontation between the opposing personalities was caused by prejudice, vengeance, jealousy, and intimidation. The research was conducted through analysis. The study demonstrated how entities portrayed in favorable and negative characters revealed radically different realities depending on the point of view. The study found that prejudice can occasionally play a vital part in enhancing someone's attitude, manner, and behavior based on the conflict between the major characters, Mr. Darcy and Elisabeth. According to the deconstruction, jealousy might assist someone in understanding that she or he possesses something exceedingly precious.Keywords: Deconstruction, Opposition, Characters, and Literary Critics.